Trichoderma carraovejensis: a new species from vineyard ecosystem with biocontrol abilities against grapevine trunk disease pathogens and ecological adaptation - Zanfaño, Laura; Carro-Huerga, Guzmán; Rodríguez-González, Álvaro; Mayo-Prieto, Sara; Cardoza, Rosa E.; Gutiérrez, Santiago; Casquero, Pedro A. (Frontiers in Plant Science, 2024)
Trichoderma strains used in vineyards for the control of Grapevine Trunk Diseases (GTDs) present a promising alternative to chemical products. Therefore, the isolation and characterization of new indigenous Trichoderma strains for these purposes suppose a valuable strategy to favor the adaptation of these strains to the environment, thus improving their efficacy in the field. In this research, a new Trichoderma species, Trichoderma carraovejensis, isolated from vineyards in Ribera de Duero (Spain) area, has been identified and phylogenetically analyzed using 20 housekeeping genes isolated from the genome of 24 Trichoderma species. A morphological description and comparison of the new species has also been carried out. In order to corroborate the potential of T. carraovejensis as a biological control agent (BCA), confrontation tests against pathogenic fungi, causing various GTDs, have been performed in laboratory. The compatibility of T. carraovejensis with different pesticides and biostimulants has also been assessed. This new Trichoderma species demonstrates ability to control pathogens such as Diplodia seriata, as well as high compatibility with powdered sulfur-based pesticides. In conclusion, the autochthonous species T. carraovejensis can be an effective alternative to complement the currently used strategies for the control of wood diseases in its region of origin.